Telling stories: Credibility and the representation of social actors in Australian asylum appeals. (September 2017) - Smith-Khan, Laura
To secure protection in the global North, asylum-seekers must overcome restrictive government policies and present a convincing refugee narrative. Their credibility becomes their main asset and must survive the multiple challenges arising from intercultural communication and interactions involving multiple institutional actors. Aiming to explore the impact institutional understandings of refugee narrative creation have on credibility assessment, I present the findings of an analysis of a corpus of documents from the Australian tribunal responsible for the administrative review of asylum decisions. I critically analyse these texts to identify how the tribunal and its agents discursively present the various actors involved in asylum appeals. I argue that despite the cautions of existing scholarship, these texts present the asylum-seeker as the sole author of the final refugee narrative, regardless of the role that decision-makers and other actors, such as lawyers and interpreters, play in its co-construction. Thus, the institution places disproportionate responsibility on the asylum-seeker for communication outcomes, creating significant challenges for their credibility.